Bioconversion of Organic Waste into Maggots as a Substitute for Chicken and Fish Feed at The Trisula Jaya Farmers Group in Tangerang to Support Sustainable Food Security - Fifit Astuti; Nur Rohmat; Oky Supriadi (Unram Journal of Community Service, 2025)
Feed is a crucial requirement in the livestock sector, whether for cattle, fish, chickens, or birds. Frequently rising feed prices make it difficult for farmers to meet their livestock's needs. This also presents a problem for the Trisula Jaya Farmer Group, which focuses on chicken and catfish farming. On the other hand, organic waste production in the community is increasing. Considering these two issues, the Trisula Jaya Farmer Group conducted community service activities to meet the need for animal feed by converting organic waste into animal feed. The community service methods implemented included the use of organic waste shredding machines, drying machines, flouring machines, and temperature and humidity monitoring systems using IoT technology. In addition to implementing organic waste processing technology into maggots, processing maggots into animal feed, using temperature and humidity monitoring systems using IoT technology, training was also conducted on how to operate organic waste processing machines, maggot processing, and using temperature and humidity monitoring systems using IoT technology. Based on the results of the application of technology to process organic waste into maggots and convert them into animal feed using a temperature and humidity monitoring system using IoT technology, the maggots processing has been significantly helpful for the Trisula Jaya Farmer Group in providing feed for the livestock they cultivate.